A Study of the Section 12J Venture Capital Company Regime as a Capital Procurement Instrument for Small Medium and Micro Enterprises - Legwaila, Thabo (University of Pretoria, 2015)
Mini Dissertation (LLM)--University of Pretoria, 2014.